Tradisi Tahlilan sebagai Akulturasi Budaya dan Agama - Naili Sahila Rohmah; A. Halil Thahir; Moh. Muwaffiqillah; Zainal Muttaqin (Gunung Djati Conference Series, 2023)
There are various kinds of culture in Indonesia related to Islam, one of which is tahlilan. Before the existence of Islam in Indonesia, society was very much bound by traditions passed down from generation to generation, and was a religion taught by Hindu-Buddhist religions. Until Islam spread widely, which was spread by Wali Songo. They spread Islam by inserting the teachings of Islam in traditions that are already attached to society. Until now, we still often encounter tahlilan in Indonesia, but there are some people who are starting to leave tahlilan. They think that tahlilan is a bid`ah tradition, because it was not taught at the time of the Prophet. But there are also those who think that the tahlilan tradition already has its foundation from the Qur'an and the hadith of the prophet. In conclusion, tahlilan is one of the acculturation of Islamic culture and religion, which aims to convey sympathy and empathy for families who have been stricken by death. Tahlilan is a syar`i tradition or in other words, it is a traditional shari`at.